Methadone Suppresses Neuronal Function and Maturation in Human Cortical Organoids - Wu, Wei; Yao, Hang; Dwivedi, Ila; Negraes, Priscilla D.; Zhao, Helen W.; Wang, Juan; Trujillo, Cleber A.; Muotri, Alysson R.; Haddad, Gabriel G. (Frontiers in Neuroscience, 2020)
Accumulating evidence has suggested that prenatal exposure to methadone causes multiple adverse effects on human brain development. Methadone not only suppresses fetal neurobehavior and alters neural maturation, but also leads to long-term neurological impairment. Due to logistical and ethical issues of accessing human fetal tissue, the effect of methadone on brain development and its underlying mechanisms have not been investigated adequately and are therefore not fully understood. Here, we use human cortical organoids which resemble fetal brain development to examine the effect of methadone on neuronal function and maturation during early development. During organoid development, cortical organoids, exposed to clinically relevant concentrations of methadone, exhibited suppressed maturation of neuronal function. For example, organoids developed from 12th week till 24th week have an about 7-fold increase in AP firing frequency, but only half and a third of this increase was found in organoids exposed to 1 μM and 10 μM methadone, respectively. We further demonstrated substantial increases in INa (4.5 fold) and IKD (10.8 fold), and continued shifts of Na+ channel activation & inactivation during normal organoid development. Methadone-induced suppression of neuronal function was attributed to the attenuated increase in the densities of INa and IKD and the reduced shift of Na+ channel gating properties. Since normal neuronal electrophysiology and ion channel function are critical for regulating brain development, we believe that the effect of prolonged methadone exposure contributes to the fetal brain delayed maturation, development and potentially for longer term neurologic deficits.